Food Security Incidences Based on Dietary Energy Consumption, Dietary Diversity and Household Food Insecurity Access Scale in Chamwino District, Tanzania - Assenga, Emiliana A; Kayunze, Kim A (International Journal of Asian Social Science, 2016)
Dietary energy consumption (DEC), dietary diversity (DD) and household food insecurity access scale (HFIAS) are used in determining food security. However, it is not known whether their uses give similar incidences of food security. The study on which this paper is based sought to determine food security based on the above methods, with the specific objectives to: a) determine DEC per adult equivalent and per capita both per day, b) determine household dietary diversity, c) measure food access by using HFIAS and (d) compare food security incidences based on the four methods of food security determination. Random sampling was used to select 400 households. The research was a cross sectional one and was conducted through structured interviews using a questionnaire, focus group discussions and key informant interviews. Using DEC per adult equivalent and per capita both per day, it was found that 84.2% and 81.8% of the 400 sampled households were food secure respectively. Using HFIAS and DD, 88% and 31.8% were food secure respectively. It is concluded that DEC per adult equivalent per day, per capita per day and HFIAS give almost similar food security incidences and have good potential to give reasonable results of food security status, while DD tends to exaggerate food insecurity incidences. It is recommended that the government and other stakeholders dealing with food security should use both DEC per adult equivalent, DEC per capita per day and HFIAS almost equally since they give almost similar results. Besides, effort should be made to establish international cut off points and food items to include in the classification of households into food secure and food insecure based on DD.